Safety and immunogenicity of a modified mRNA-lipid nanoparticle vaccine candidate against COVID-19: Results from a phase 1, dose-escalation study - Brandon J. Essink; Craig Shapiro; Marie Grace Dawn Isidro; Paul Bradley; Antoinette Pragalos; Mark Bloch; Joel Santiaguel; Melchor Victor Frias; Spiros Miyakis; Margarida Alves de Mesquita; Stefano Berrè; Charlotte Servais; et al. (Taylor & Francis Group, 2024)
This phase 1, open-label, dose-escalation, multi-center study (NCT05477186) assessed the safety and immunogenicity of a booster dose of an mRNA COVID-19 vaccine (CV0501) encoding the SARS-CoV-2 Omicron BA.1 spike protein. Participants aged ≥ 18 years previously vaccinated with ≥ 2 doses of an mRNA COVID-19 vaccine received CV0501 doses ranging from 12 to 200 μg. After assessment of safety and immunogenicity of the 12 μg dose in 30 adults, 30 adults ≤ 64 years were randomized to receive either a 3 or 6 μg dose. Solicited adverse events (AEs) were collected for 7 days, unsolicited AEs for 28 days, and serious AEs (SAEs), medically attended AEs (MAAEs), and AEs of special interest (AESIs) until day (D) 181 post-vaccination. Serum neutralizing titers specific to SARS-CoV-2 BA.1, wild-type, Delta, and additional Omicron subvariants were assessed at D1, D15, D29, D91, and D181. Of 180 vaccinated participants (mean age: 49.3 years; 57.8% women), 70.6% had prior SARS-CoV-2 infection. Most solicited local (98.1%) and systemic (96.7%) AEs were of mild-to-moderate severity; the most common were injection site pain (57.5%; 33.3-73.3% across groups) and myalgia (36.9%; 13.3-56.7%). Unsolicited AEs were reported by 14.4% (6.7-26.7%) of participants (mild-to-moderate severity in 88.5% of the participants). Three participants (1.7%) reported SAEs, 16.7% (6.7-30.0%) reported MAAEs, and 8.3% (0.0-13.3%) reported AESIs (15 COVID-19 cases), none related to vaccination. Geometric means of serum neutralizing titers increased from baseline to D15 and D29 (dose-dependent), and then decreased over time. The safety and immunogenicity results supported advancement to a phase 2 trial.